2017
DOI: 10.1107/s1600576717007312
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation of protein crystals as a race against time with on- and off-pathways

Abstract: High supersaturation levels are a necessary but insufficient condition for the crystallization of purified proteins. Unlike most small molecules, proteins can take diverse aggregation pathways that make the outcome of crystallization assays quite unpredictable. Here, dynamic light scattering and optical microscopy were used to show that the nucleation of lysozyme crystals is preceded by an initial step of protein oligomerization and by the progressive formation of metastable clusters. Because these steps deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Pre-filtration of the insulin solution using 0.22 μm syringe filters efficiently removed these particles (Figure S2), but it also delayed the onset of the fibrillation process until a point where the kinetic measurements of Foderà et al [26] could not be reproduced anymore. Therefore, pre-assembled protein clusters act as important heterogeneous nucleation centers without which the rapid formation of ordered aggregates is compromised [37,38,39]. The low concentration of the insulin clusters (fraction of total protein <1010 estimated from the initial PSDs) is high enough to conceal the initial progress of fibril sizes expected to start at R*=5.7 nm and not from R¯h values greater than 100 nm (compare dashed lines and experimental values in Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Pre-filtration of the insulin solution using 0.22 μm syringe filters efficiently removed these particles (Figure S2), but it also delayed the onset of the fibrillation process until a point where the kinetic measurements of Foderà et al [26] could not be reproduced anymore. Therefore, pre-assembled protein clusters act as important heterogeneous nucleation centers without which the rapid formation of ordered aggregates is compromised [37,38,39]. The low concentration of the insulin clusters (fraction of total protein <1010 estimated from the initial PSDs) is high enough to conceal the initial progress of fibril sizes expected to start at R*=5.7 nm and not from R¯h values greater than 100 nm (compare dashed lines and experimental values in Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of convection on the protein growth mechanism may be manifold. Novel investigations suggest that the protein molecules can form oligomers already in the crystallization solution [63], rather than entering the crystal lattice one-by-one. Ferreira et al [63] thought that the mesoscopic clusters are beneficial when they accelerate the formation of the first precrystalline nuclei and are detrimental as they deplete the solution of protein ready to crystallize.…”
Section: The Morphologies Of the Grown Lysozyme Crystalsmentioning
confidence: 99%
“…Novel investigations suggest that the protein molecules can form oligomers already in the crystallization solution [63], rather than entering the crystal lattice one-by-one. Ferreira et al [63] thought that the mesoscopic clusters are beneficial when they accelerate the formation of the first precrystalline nuclei and are detrimental as they deplete the solution of protein ready to crystallize. Nadarjah et al [64] thought that the growth of a protein crystal was a two-step process: aggregate growth units are first formed in the bulk solution by stronger intermolecular bonds and then attached to the crystal face by weaker bonds.…”
Section: The Morphologies Of the Grown Lysozyme Crystalsmentioning
confidence: 99%
“…Sleutel and van Driessche (2014) 5 showed evidence that clusters are liquid-like and metastable concerning the emerging crystalline phase (e.g., lysozyme and insulin). Ferreira et al (2017) 10 demonstrated the existence of clusters that do not give rise to crystals and remain in solution (lysozyme). Kaissaratos et al (2021) 8 also stated that two-step nucleation is a phase transformation over the classical pathway due to a lower surface-free energy barrier.…”
Section: Introductionmentioning
confidence: 99%